The evolution of a Precambrian arc-related granulite facies gold deposit: Evidence from the Glenburgh deposit, Western Australia - Roche, L.; Korhonen, F.; Johnson, S.; Wingate, M.; Hancock, E.; Dunkley, Daniel; Zi, Jianwei; Rasmussen, Birger; Muhling, Janet; Occhipiniti, S.; Dunbar, M.; Goldsworthy, J. (Elsevier BV, 2017)
Gold deposits are rare in upper-amphibolite to granulite facies environments. Known examples commonly attract debate about whether they formed under these conditions or instead represent metamorphosed, metasomatic, or superimposed (retrograde) mineralization. The Glenburgh gold deposit is located in the Paleoproterozoic upper-amphibolite to granulite facies Glenburgh Terrane in the southern Gascoyne Province of Western Australia. Gold at the Glenburgh deposit is free and disseminated within quartz–biotite–garnet gneiss, amphibolite, and (post-gold) quartz–chlorite veins. No clear association with a specific host lithology has been identified and mineralization does not have a visually distinct proximal alteration assemblage. The rocks hosting the deposit represent a distinct sedimentary package that was deposited, mineralized, buried, and metamorphosed, all during arc magmatism. Features within the internal structure of gold grains, such as high-purity gold veinlets, incoherent twinning, and low silver content, suggest the gold has been through post-depositional processes such as metamorphism and deformation. Abundant sulfide minerals are interpreted to have formed by sulfidation of the host rock contemporaneously with gold mineralization, and the presence of rounded sulfide inclusions within garnet porphyroblasts illustrates the presence of a sulfide phase prior to peak metamorphism. Geochronology of zircon and monazite constrains the timing of mineralization to be younger than c. 2035 Ma—the maximum depositional age of the metasedimentary host rocks—but older than c. 1991 Ma—the peak of M1 metamorphism during the Glenburgh Orogeny; these events were synchronous with arc magmatism. Rocks at the Glenburgh deposit were likely deposited in a fore-arc or accretionary wedge, a favourable setting for porphyry Cu–Mo–Au, epithermal Au, polymetallic (Sn, W) skarn, and orogenic Au mineralization. Phase equilibria modelling of a pelitic migmatite constrains peak P–T conditions to be 865–885 °C, 6.8–7.6 kbar, consistent with elevated thermal gradients within the arc, followed by conductive cooling of arc magmas. Partial melting during peak M1 metamorphism possible caused gold remobilization. The lack of an alteration assemblage further suggests that the alteration assemblage and mineralization were recrystallized during deformation and metamorphism. However, increases in Ca and K abundance and magnetic susceptibility decreases toward mineralization, suggesting that they may constitute ore vectors.